2016
DOI: 10.1155/2016/3917471
|View full text |Cite
|
Sign up to set email alerts
|

New Role of Adult Lung c-kit+Cells in a Mouse Model of Airway Hyperresponsiveness

Abstract: Structural changes contribute to airway hyperresponsiveness and airflow obstruction in asthma. Emerging evidence points to the involvement of c-kit+ cells in lung homeostasis, although their potential role in asthma is unknown. Our aim was to isolate c-kit+ cells from normal mouse lungs and to test whether these cells can interfere with hallmarks of asthma in an animal model. Adult mouse GFP-tagged c-kit+ cells, intratracheally delivered in the ovalbumin-induced airway hyperresponsiveness, positively affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 64 publications
2
14
0
Order By: Relevance
“…Consistent with our results, Spaziano and co-workers the intratracheal administration of 5 × 10 4 murine pulmonary c-kit cells had potential to suppress the production of cytokines IL-4, -5, and -13 with polarization of macrophages to M2-like phenotype orchestrated possibly in paracrine and/or juxtacrine manner. In addition, the local content of IL-10 was also increased post-c-kit transplantation [26] . The advantage of the current experiment is to investigate the potent anti-asthmatic activity of bone marrow c-kit cells (3 × 10 5 cell) compared to local c-kit lineage and to highlight the underlying role of distinct mi-RNAs in pulmonary tissue.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Consistent with our results, Spaziano and co-workers the intratracheal administration of 5 × 10 4 murine pulmonary c-kit cells had potential to suppress the production of cytokines IL-4, -5, and -13 with polarization of macrophages to M2-like phenotype orchestrated possibly in paracrine and/or juxtacrine manner. In addition, the local content of IL-10 was also increased post-c-kit transplantation [26] . The advantage of the current experiment is to investigate the potent anti-asthmatic activity of bone marrow c-kit cells (3 × 10 5 cell) compared to local c-kit lineage and to highlight the underlying role of distinct mi-RNAs in pulmonary tissue.…”
Section: Discussionmentioning
confidence: 92%
“…Of most notably, c-kit + cells belonging to stem cells have been shown to possess unique regenerative capacity and immuno-modulatory effects in animal cardiac tissues [22][23][24][25]. However, experiments and therapies based on c-kit + cells for airway in ammation are still in its infancy [26]. The current study targets to reveal the correlation between anti-in ammatory effects of c-kit positive cells and distinct miRNAs contributing to therapeutic paracrine outcome.…”
Section: Discussionmentioning
confidence: 99%
“…; Spaziano et al. ) but its effects during asthmatic airway hyperresponsiveness have not been clarified yet. Thus, we studied the role of the N/OFQ peptide in the inflammatory and remodeling process of the small airways, by using an ex vivo histological approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, histopathological evidence from several studies has clearly shown that the inflammation in asthmatic subjects also involves the small airways (Wagner et al 1998). N/ OFQ protects against bronchial hyperresponsiveness and has immunomodulatory properties in the lung (Saetta et al 1985;Wagner et al 1998;Corsico et al 2003;Sullo et al 2013;Spaziano et al 2016) but its effects during asthmatic airway hyperresponsiveness have not been clarified yet. Thus, we studied the role of the N/OFQ peptide in the inflammatory and remodeling process of the small airways, by using an ex vivo histological approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation